Bioactive compounds extracted by liquid and supercritical carbon dioxide from citrus peels. (8th April 2022) - Romano, Raffaele; De Luca, Lucia; Aiello, Alessandra; Rossi, Danilo; Pizzolongo, Fabiana; Masi, Paolo
Abstract: This work investigated the extraction of bioactive compounds from citrus peels, an agri‐food waste. Carbon dioxide (CO2 ), an eco‐friendly solvent, was used under liquid and supercritical conditions to perform the extractions from orange, tangerine and lemon peels. The possibility of using ethanol as a cosolvent at small percentages up to 20% was also studied. The extraction yield, total polyphenolic content, individual polyphenolic profile, antiradical activity and volatile organic compounds of the extracts were evaluated. The highest yields were obtained when 20% ethanol was used as a cosolvent in both liquid (at 20 MPa and 20 °C) and supercritical (at 30 MPa and 60 °C) CO2 extraction. In addition, the extracts obtained with liquid CO2 + 20% ethanol showed the highest content of naringin (35.26, 44.05 and 19.86 mg g ‐1 in orange, tangerine and lemon peel extracts, respectively) and terpenes, in particular limonene. This type of extract also showed the highest antiradical activity (31.78–59.51 µmolTE g ‐1 ) as measured by both ABTS·+ and DPPH·. These findings show that the extraction with a liquid CO2 and ethanol mixture could be a valid alternative to traditional solvent extraction using 80% less organic solvent and producing extracts with high antiradical capacity and rich in volatile organic compounds. Abstract : Extraction by liquid CO2 produced extracts with high antioxidant activity and high content of naringin, flavonoids, limonene and total polyphenols.